Transformative Islamic Religious Education and Developing Students’ Character: An Analysis of Paulo Freire’s Critical Pedagogy - Wirda Ningsih; Yundri Akhyar (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2026)
This study explores the transformative application of Paulo Freire’s Critical Pedagogy within the framework of Islamic Religious Education. The issue addressed in this research arises from the need to reform Islamic education from a traditional, teacher-centred model toward one that cultivates critical thinking, social awareness, and moral character. The purpose of this study is to analyze how Freire’s principles, particularly critical consciousness, dialogical learning, and empowerment, can be implemented to strengthen students’ reflective, moral, and participatory character development in alignment with Islamic values. Using a library research method, data were collected through a review of relevant literature, including books, journal articles, and previous studies discussing Freire’s pedagogy and its adaptation in Islamic contexts. The findings indicate that integrating Freire’s critical pedagogy into Islamic education strengthens students’ reflective and moral reasoning while maintaining spiritual authenticity. This approach also fosters a democratic and participatory learning environment that encourages students to question, analyze, and transform their social realities in accordance with Qur’anic principles. However, challenges such as resistance to pedagogical change and the dominance of rote learning traditions remain significant. The study highlights the potential of critical pedagogy as a bridge between faith-based learning and contemporary educational reform, encouraging Islamic educators to cultivate learners who are both devout and critically conscious. The impact of this research lies in offering a critical-integrative framework that merges Islamic epistemology with Freirean pedagogy to promote transformative character education